Thermal Modelling of CubeSats in ESATAN-TMS - Nijenhuis, A.K. te; Brouwer, H.S.B.; Jonsson, M.; Bloem, E.A.; Benthem, R.C. van; Volmuller, G.J. (Netherlands Aerospace Centre NLR, 2020)
Miniaturization has allowed CubeSats to enter the domains of Earth observation, RF-oriented missions, and astronomy, surpassing its original intention of being an educational instrument. With the increase in power density, thermal control measures are needed for CubeSats, requiring low-cost hardware and software solutions, which are currently hardly available. The deficit of thermal control solutions for CubeSats is inherently related to their short development time resulting in suboptimal thermal designs. Miniaturization and application of thermal control systems is being worked on (1,2), however evaluating design iterations is hindered by the lack of thermal analysis imposing large uncertainties in the thermal design of CubeSats. The conventional method of validation and model correlation to reduce model uncertainties takes too much time and is therefore excluded for CubeSats. ISIS - Innovative Solutions in Space and the Royal Netherlands Aerospace Centre, NLR have worked together on an innovative modular approach for CubeSat thermal analyses in ESATAN-TMS. Key of this approach is the interchangeability and scalability of validated thermal sub-models allowing for fast and more accurate analysis for LEO missions. Any design of a CubeSat can be quickly evaluated in ESATAN-TMS by implementation of a combination of validated and correlated thermal sub-models in the CubeSat frame model. Over time a library of validated thermal sub-models will be created in ESATAN-TMS, allowing for fast and accurate orbital analysis, which results in improved thermal designs of CubeSats.
A Modular Approach
This report is based on a presentation that was planned to be held at the 50th International Conference on Environmental Systems, in Lisbon, 12th -16th of July 2020. However, due to COVID-19, the conference was postponed to 2021, but the proceedings for 2020 were still published.
Keywords: Space technology